The Challenges Of Implementing The Physical Education Curriculum In The Physical Education Learning Process In High School - Mulia, Saini; Amir, Nyak; Ismail, Razali; Syahruddin, syahruddin; Sukiri, Sukiri (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
This study aims to determine the challenges in implementing the physical education curriculum in high school. This study uses a qualitative descriptive research design to find out information and descriptions about the implementation of the physical education curriculum in high school. The subjects in this study were physical education teachers at high school in Aceh Tengah district, Aceh province, Aceh province. The data in this study were obtained based on the output of interviews with respondents. Data analysis consists of data collection, data reduction, data presentation or display, and drawing conclusions. The conclusions from this study are: (1) The implementation of the physical education curriculum in high school is not optimal, it is indicated from the learning process where physical education teachers have not been able to carry out systematic learning starting from planning, implementation and evaluation, in addition to the learning process that have not used the scientific approach. The challenge for the physical education curriculum in high school is the lack of teacher knowledge regarding the concept of the physical education curriculum, so that it has an impact on the implementation of the curriculum that is not optimal